Application of The AWBA Method in Oyster Mushroom Farmers to Reduce Work-related Musculoskeletal Disorders - Lina Dianati Fathimahhayati; Theresia Amelia Pawitra; Willy Tambunan; Markus Hartono; Fisca Riana Sari (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
WMSD frequently occurs in agriculture works, because the working conditions that require awkward posture in standing or sitting position as well as lifting and carrying heavy loads. Preliminary study showed that oyster mushroom farmers experienced pain in several of body parts especially their waist.  Therefore, this paper aims to evaluate the working posture of oyster mushroom farmers using AWBA (Agriculture Whole Body Assessment) and provide recommendation to reduce risk of musculoskeletal disorder. AWBA evaluates working posture and duration of upper (AULA) and lower extremities (ALLA). The result showed that activity of oyster mushroom production was risky, since 46,7% of all activities were categorized as “very high” and “high” level. Skor of AWBA posture correlated significantly with ALLA (0.812) and and AULA (0,56). Regression analysis showed that AWBA positively correlated with AULA and ALLA. Duration analysis showed that 86,7% working duration were classified as “very high”. The riskiest activity was harvested mushroom from top shelf. Furthermore, distribution and mixing raw materials, taking out baglog from sterilizer, harvesting mushroom from middle shelf, and packaging mushroom into plastic bag also risky activities, since the duration and posture measurement were classified as very high and high, respectively. Recommendation for reducing WMSD were redesigning working area and facilities of oyster mushroom production, such as design ergonomics baglogs’ shelves so that farmers position when reached the baglog was neutral, utilizing table and chair with suitable height in filling media into baglog, inoculation, releasing baglogs’ ring, and packaging activities.